Socio-demographic inequalities and teeth extraction in the last 12 months in Italy - La Torre, Giuseppe (Ann Stomatol (Roma), 2015)
AIMS: Teeth loss represents a major concern for the global oral health status of a population. The aim of this study was to describe the prevalence of teeth extraction among the Italian adult population, analyzing the association between teeth extraction in the last 12 months and socio-demographic characteristics. METHODS: This cross-sectional study is based on the national survey ‘Health Conditions and Healthcare Services Use’, carried out by the Italian National Centre of Statistics (ISTAT) in 2005. A univariate analysis was performed to investigate the association between the dependent and the independent variables (teeth extraction Vs socio-demographic characteristics). Multiple logistic regression analysis was conducted to assess the influence on the outcome (teeth extraction Yes/No). RESULTS: The present study highlights the relationship between teeth extraction and socio-demographic factors. Out of 128,040 individuals, the sampled population consisted of 124,677 subjects, representing 56,400,323 individuals in the Italian population. The prevalence of teeth extraction in the last 12 months was 8.2%. Subjects who underwent teeth extraction in the last 12 months were prevalent female (8.6%), smokers (10.4%), with a primary education (9.2%), married (9.2%), in poor health conditions (9.3%), age category of 55–64 years (11.1%), from Northeast of Italy (8.5%), with scarce household income (8.4%). The multivariate analysis confirmed most of the results of the univariate analysis. CONCLUSIONS: Inequalities in health among groups of various socioeconomic status constitute one of the main challenges for public health; these inequalities might be reduced by improving educational opportunities, income distribution, health-related behaviour, or accessibility to health care.